The Babylonian astronomical compendium MUL.APIN - Hunger, Hermann 1942-; Steele, John M. (Scientific writings from the ancient and Medieval world, 2019)
About the MUL.APIN: astronomical data and lists of stars, from ancient Mesopotamia